2013
DOI: 10.1097/mib.0b013e3182802b87
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Small Bowel Crohn’s Disease

Abstract: BS and MR enterography are 2 accurate procedures for the diagnosis of small bowel CD, although MR seems to be more sensitive in defining its extension. BS could be used to select the patients for subsequent MRI examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(41 citation statements)
references
References 51 publications
3
36
1
1
Order By: Relevance
“…Our study agreed with different trials in which it was shown that detection rate of fistulas, depending on their localization, had sensitivity between 67% and 82% and specificity between 90% and 100%[ 8 , 9 , 21 - 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study agreed with different trials in which it was shown that detection rate of fistulas, depending on their localization, had sensitivity between 67% and 82% and specificity between 90% and 100%[ 8 , 9 , 21 - 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…A bowel wall thickness cutoff value of 3 mm in our study showed sensitivity (83.3%), specificity (50%), and accuracy (60%) in comparison to other studies, which showed sensitivities of 88% to 94%; however, specificity (93%-97%,) and diagnostic accuracy (94%) were higher in previous studies than in our study[ 9 , 15 ]. This finding can be explained by the lack of international agreement about standardized measurement parameters, which leads to interobserver variability between examiners[ 18 ].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Reference standards may also be applied inconsistently, with endoscopy, surgery and imaging all variably employed. For example, in a comparative study with US, Castiglione et al 31 used MRE without any additional reference standard in many recruits. The potential for incorporation bias is self-evident.…”
Section: Discussionmentioning
confidence: 99%
“…By way of example, in the largest study of US to date (296 participants), 30 the standard of reference was simple barium fluoroscopic studies in > 70% of recruited participants. Similarly, in their single-centre comparative study of MRE and US in 249 participants with suspected CD (120 with a confirmed diagnosis), Castiglione et al 31 used MRE itself as the standard of reference for small bowel Crohn's disease (SBCD) extent in the majority of participants who did not have surgical reference standard, clearly risking incorporation bias. There is no single reference standard for defining the location, extent and activity of CD.…”
Section: Existing Literature On the Diagnostic Accuracy Of Magnetic Rmentioning
confidence: 99%